Data science from scratch : the #1 data science guide for everything a data scientist needs to know: Python, linear algebra, statistics, coding, applications, neural networks, and decision trees - Cooper, Steven ([Place of publication not identified]: Data Science, 2018)
This book provides an in depth information about what data science is and why it is important. Topics covered include: the prerequisites you will need to get started in data science; what it means to be a data scientist; the roles that hacking and coding play in data science; the different coding languages that can be used in data science; why python is so important; how to use linear algebra and statistics; and the different applications for data science.
Includes bibliographical references
lje 11/01/2019, ijb, 28/01/2019
Loans
Keywords: Big data; Machine learning; Data mining